Potentiation of Doxorubicin Cytotoxicity Utilizing Clarithromycin Loaded-PEGylated Liposomes - Islam Alfreahat MS; Hamdi Nsairat PhD; Ibrahim Deeb Aldeeb PhD; Ali Al-Samydai PhD; Walhan Alshaer PhD (Technology in Cancer Research & Treatment)
Background Doxorubicin (DOX) is a potent chemotherapeutic agent for breast cancer, but its effectiveness is often diminished by resistance mechanisms, particularly through p-glycoprotein (P-gp) mediated drug efflux. Clarithromycin (CAM), a macrolide antibiotic, inhibits multiple metabolic pathways including CYP3A and P-gp, potentially countering DOX resistance. Objective This study aimed to evaluate the potentiation of DOX and its effectiveness against the MCF-7 breast cancer cell line by encapsulating both DOX and CAM in PEGylated liposomes. Methods PEGylated liposomes containing DOX and CAM were prepared using the thin film hydration method. The physicochemical properties of the liposomes, including average particle size, polydispersity index (PDI), and zeta potential, were characterized. Encapsulation efficiencies for CAM and DOX were assessed, and stability of the liposomes was evaluated over 9 days at room temperature. Cell viability was measured using an IC 50 assay, and P-gp expression levels were determined by ELISA. Results The CAM/DOX-PEGylated liposomes exhibited optimal average particle size (238 ± 26.7 nm), PDI (0.29 ± 0.107), and zeta potential (−20.9 ± 2.17 mV). These liposomes maintained good stability regarding size and charge over 9 days. Encapsulation efficiencies were 81.05% for CAM and 78.13% for DOX. The IC50 value for CAM/DOX-PEGylated liposomes was 0.13 µM, representing a significant reduction compared to the physical mixture of CAM and DOX (0.25 µM) and free DOX (0.21 µM) against MCF-7 cells. ELISA analysis showed a reduction in P-gp expression of approximately 5% with CAM/DOX-PEGylated liposomes compared to 1.61% with free DOX. Conclusion The results indicate that CAM encapsulated in PEGylated liposomes enhances the effectiveness of DOX against breast cancer cells, likely through the inhibition of p-glycoprotein. This approach may offer a promising strategy to overcome DOX resistance and improve chemotherapy outcomes.